PERANGKAT LUNAK PENCATATAN PAJAK PADA BAGIAN AKUNTANSI (STUDI KASUS : PT STILUS UTAMA MATERIALS BANDUNG) - Heri Purwanto; Mochamad Cory Sakti Triwangsa; Chika Gustiana Widiarestuwati (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
This study aims to design software that will be used in the accounting department with a function to record client transactions according to existing business processes with the aim of being able to provide information about client receivables precisely and accurately and can avoid the accumulation of client receivable documents, minimizing loss client data, research methods use qualitative methods and the data needed to design software are obtained from interviews and observations, the approach used to obtain results is to develop applications used in this study using a prototype method that produces web-based software using the laravel framework with research results presented in the form of a prototype in the form of a web application using the laravel framework included with application development guidelines such as use cases, activity diagrams, class diagrams, database design, user int mockups interface, as well as the finished application. The application has been tested on a computer with predetermined specifications and black box testing has been carried out in which several functions have been determined previously as a result of black box testing. shows that the application runs as designed and can replace the current business processes of PT. Stylus Utama Materials Bandung and can minimize the loss of client data in accordance with the research objectives. for further research, the program will be made on other platforms such as node js or mobile and performance comparisons can be made with laravel on the node js platform or in the mobile version.